Eplerenone for early cardiomyopathy in Duchenne muscular dystrophy: results of a two-year open-label extension trial. Issue 1 (December 2017) - Raman, Subha; Hor, Kan; Mazur, Wojciech; He, Xin; Kissel, John; Smart, Suzanne; McCarthy, Beth; Roble, Sharon; Cripe, Linda
Abstract Background Cardiomyopathy is a leading cause of morbidity and mortality in boys with Duchenne muscular dystrophy (DMD). We recently showed in a 12-month double-blind randomized controlled trial that adding eplerenone to background medical therapy was cardioprotective in this population. The objective of this study was to evaluate the safety and efficacy of longer-term eplerenone therapy in boys with DMD. Results Eleven subjects (phase 1 baseline median [range] age: 13 [7 – 25] years) from the original 12-month trial at a single participating center were enrolled. Importantly, those who entered the extension study who had been on eplerenone previously were significantly older than those who had originally been on placebo (median age 10.5 vs. 18.0 years, p  = 0.045). During an additional 24-month open-label extension study, all boys received eplerenone 25 mg orally once daily to treat preclinical DMD cardiomyopathy, defined as evident myocardial damage by late gadolinium enhancement cardiac magnetic resonance (LGE) with preserved ejection fraction (EF). The threshold for potassium level, the primary safety measure, was not exceeded in any non-hemolyzed blood sample. Over 24 months, left ventricular (LV) systolic strain, a more sensitive marker whose more negative values indicate greater contractility significantly improved (median change -4.4%, IQR -5.8 to -0.9%) in younger subjects whereas older subjects' strain remained stable without significant worsening or improvement (median change 0.2%, IQR -1.1 to 4.3%). EF and extent of myocardial damage by LGE remained stable in both groups over 2 years. Conclusions Eplerenone offers effective and safe cardioprotection for boys with DMD, particularly when started at a younger age. Eplerenone is a useful clinical therapeutic option, particularly if treatment is initiated earlier in life when cardiac damage is minimal. Trial registration http://ClinicalTrials.gov identifier NCT01521546. Registered 26 January 2012.